2011
DOI: 10.1016/j.jastp.2011.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of daytime ionosphere behavior between 2004 and 2008 in Antarctica

Abstract: In this paper we present 5Ͳyear study of the lower ionosphere behavior obtained from VLF sounding done at Comandante Ferraz Brazilian Antarctic Station. The results suggested a strong influence of 'meteorological processes' especially during wintertime, when VLF measurements showed that the DͲ region was strongly affected by planetary waves in all years. This effect was superposed to the well known control by solar radiation. The 16Ͳday wave was the most important PW modulating the lower ionosphere behavior. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…The first comparison between VLF NB amplitude and the SABER temperature profile showed that in most cases the highest anticorrelation was between the NB amplitudes and mesopause temperatures. Although VLF NB amplitudes were already associated in previous studies to the dynamics and temperatures of the stratosphere [e.g., Correia et al ., ], the relation between VLF NB amplitudes and mesopause temperatures, either direct or indirect, has not been identified previously. However, a connection between mesopause temperatures and radio waves absorption has been predicted before [e.g., Taubenheim , ].…”
Section: Discussionmentioning
confidence: 99%
“…The first comparison between VLF NB amplitude and the SABER temperature profile showed that in most cases the highest anticorrelation was between the NB amplitudes and mesopause temperatures. Although VLF NB amplitudes were already associated in previous studies to the dynamics and temperatures of the stratosphere [e.g., Correia et al ., ], the relation between VLF NB amplitudes and mesopause temperatures, either direct or indirect, has not been identified previously. However, a connection between mesopause temperatures and radio waves absorption has been predicted before [e.g., Taubenheim , ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the annual VLF signal amplitude variation is not a fixed function of the noon solar zenith angle. Instead, it varies from year to year through the solar cycle as can be seen in Correia et al (2011). The influence of Lyα radiation on diurnal DHO VLF signal amplitude variations is visible the in the Figure 1 through the duration of daytime sections "D" and their changes during the year as seen in the Figure 2.…”
Section: Seasonal Variationsmentioning
confidence: 89%
“…As numerous studies have shown, all these parameters are variable in space and time and they can be calculated from experimental data obtained by various observational techniques. Thus, variations in the Lyα irradiance during solar cycles and seasons are presented in Woods et al (2000), Fröhlich (2009) and Correia, Kaufmann, Raulin, Bertoni, and Gavilan (2011) and results given in Kockarts (2002) exhibit a strong zenith angle dependency of Lyα line absorption coefficients in the atmosphere. Also, measurements of the NO density show values within a wide range at fixed altitudes (Aikin, Kane, & Troim, 1964;Pearce, 1969;Barabash, Osepian, Dalin, & Kirkwood, 2012; and references therein).…”
Section: Introductionmentioning
confidence: 93%
“…AGWs have been detected as amplitude variations of VLF signals associated with solar terminator motions (Nina and Cadez, 2013), with the passage of tropical cyclones crossing the transmitter-receiver VLF propagation path (Rozhnoi et al, 2014), and particularly during nighttime, in association with local convective and lightning activity (Marshall and Snively, 2014). Planetary wave signatures have also been detected in the VLF NB amplitude data, whose effects are pronounced during wintertime and present a predominant quasi 16 d oscillation (Correia et al, , 2013Schmitter, 2012;Pal et al, 2015).…”
Section: Introductionmentioning
confidence: 99%